Neurosurgery in Eastern Nepal: The Past, Present and Future and A Near Decade of Personal Experience - Roka, Yam B (Nepal Journal of Neuroscience, 2017)
Not available.Nepal Journal of Neuroscience, Vol. 14, No. 2,  2017 Page: 9-10